Manufacturing process of network ceramic / metal composite component formed based on high-temperature impregnation process

The network ceramic/metal composite component manufacturing process formed through high-temperature impregnation process solves the problem of insufficient interface bonding in ceramic/metal composite armor in three-dimensional space, and realizes a high impact resistance and lightweight ceramic/metal composite structure, which meets the needs of the Armor performance requirements for diversified combat needs.

CN119116100APending Publication Date: 2024-12-13NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505014.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing ceramic/metal composite armor is difficult to achieve effective interface combination in three-dimensional space, and cannot meet the requirements of high hardness, high strength, high toughness and low density, especially in terms of multiple bomb attacks.

Method used

The network ceramic/metal composite component manufacturing process is adopted based on the high-temperature impregnation process to design porous structures through three-dimensional modeling, combining photocuring forming and high-temperature impregnation technology to form a porous ceramic matrix, and adding copper oxide to the ceramic-metal interface to form a transition phase , enhance the interface bonding strength.

Benefits of technology

It realizes high impact resistance and lightweight of the ceramic/metal composite structure, improves the elastic modulus and compressive strength of the material, enhances the ceramic-metal interface binding force, and meets the armor performance requirements in diversified combat needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HSA0000299780230000011
    Figure HSA0000299780230000011
  • Figure HSA0000299780230000021
    Figure HSA0000299780230000021
  • Figure HSA0000299780230000022
    Figure HSA0000299780230000022
Patent Text Reader

Abstract

The invention discloses a manufacturing process of a network ceramic / metal composite component formed based on a high-temperature impregnation process, and relates to the technical field of special materials. The network ceramic / metal composite component comprises a porous ceramic matrix and solid metal filled in the ceramic matrix; the porous ceramic matrix comprises oxide ceramic and a porous structure with a controllable aperture value; the low-melting-point second phase is added into the porous ceramic matrix, so that the sintering density of the oxide ceramic is improved; according to the high-temperature impregnation technology, the porous ceramic matrix is filled with metal, meanwhile, a ceramic-transition layer-metal composite structure is formed, and the ceramic / metal interface strength is improved. Structural design is carried out on the basis of porous ceramic, the mixed metal powder is filled in a high-temperature dipping mode, the characteristics of high specific strength of ceramic and metal deformation energy absorption are achieved, compounding of materials in space is achieved, multi-material compounding and light-weight design are achieved, and wide application prospects are achieved in the fields of light-weight protective armors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special materials, and in particular to a manufacturing process for a network ceramic / metal composite component formed based on a high-temperature impregnation process. Background Art

[0002] In recent years, the strength requirements of protective armor and the lightweight requirements of equipment have been equally important. The development of a type of high-performance armor with high specific strength to meet diversified combat needs has become an important research direction in the field of armor protection. From a material perspective, in the face of the contradiction between mobility and protective performance, aluminum armor is currently the most commonly used lightweight armor material. It has the characteristics of high strength and low density, which can provide suitable resistance to armor-piercing projectiles. At the same time, it is not easy to break and is suitable for resisting fragment attacks. Ceramics have a lower density than aluminum alloys and have the characteristics of high hardness, but they are relatively brittle. For the requirements of "high hardness, high strength, high toughness, and low density" for armor materials, no homogeneous single-phase material can meet them at the same time. Ceramic / metal composite armor composed of ceramics and aluminum alloys combines tough materials and high-hardness brittle materials. It has good anti-ballistic effect and can effectively reduce the weight of armor. It can not only meet the requirements of armor resistance to single bullets, but also improve its resistance to multiple bullets. However, common ceramic / metal composite protective structures are simple laminated structures. The ceramic-metal interface properties can be improved by adding a two-dimensional transition layer, but this method is not suitable for three-dimensional continuous ceramic / metal composite structures. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention proposes a manufacturing process for a network ceramic / metal composite component formed by a high-temperature impregnation process. The technical solution of the present invention is as follows:

[0004] A method for preparing a porous ceramic substrate, characterized in that the method comprises the following steps: Step 1: Modeling: Design porous structures with different pore sizes and model the ceramic porous matrix; Step 2, slurry preparation: alumina ceramic powder and copper oxide are chemically coprecipitated to obtain mixed ceramic powder, the obtained mixed ceramic powder and alumina powder are added to a photosensitive resin and a dispersant, and mixed in a planetary ball mill to obtain a uniform slurry; Step 3, green body forming: import the model established in step 1 into the light-curing 3D printer, place the slurry obtained in step 2 into the printer, obtain the ceramic green body by light-curing forming method, place the green body in alcohol for ultrasonic cleaning for 5 minutes to remove the uncured slurry on the surface, and then place it in a UV air dryer for curing and air drying for 10 minutes to reduce the internal stress of the green body; Step 4: Degreasing and sintering: Degreasing and sintering the ceramic body obtained in step 3, and taking it out after cooling in the furnace to obtain a porous ceramic matrix.

[0005] Furthermore, the porous structure with different pore sizes in step 1 may be a lattice structure, a TPMS structure, or a Voronoi structure.

[0006] Furthermore, in the step 2, the mass ratio of the mixed ceramic powder to alumina is 4:96, the mass ratio of the total mass of the powder to the photosensitive resin is 2.5:1, the amount of dispersant added is 2% of the total mass of the powder, the speed of the planetary ball mill is 60 rpm, and the ball milling time is 60 min.

[0007] Furthermore, the debinding and sintering process parameters in step four are as follows: the heating rate in the debinding stage is 0.5°C / min, the insulation platforms are 90°C, 120°C, 160°C, 240°C, 340°C, 410°C, 500°C, and 600°C, and the insulation is performed for 120 minutes respectively; the heating rate in the sintering stage is 3°C / min, and the insulation is performed at 1600°C for 120 minutes.

[0008] Furthermore, a manufacturing process for a network ceramic / metal composite component formed by a high temperature impregnation process is characterized in that the steps of the method are as follows: Step 1: Pretreatment: Weigh a certain mass of aluminum alloy particles, grind them with silicon carbide powder, immerse them in alcohol, and use ultrasonic cleaning to remove the oxide layer on the surface; Step 2, loading: placing the aluminum alloy particles obtained in step 1 on top of the porous ceramic substrate and putting them into a graphite crucible, loading them into a furnace and placing a zirconium oxide loading block; Step 3: Gas washing: Close the furnace air inlet, turn on the vacuum pump to extract air from the exhaust port until the air pressure is close to vacuum, turn off the vacuum pump and flush argon gas from the air inlet to reach a standard atmospheric pressure, and repeat the above operation twice; Step 4: High-temperature immersion: Heat the crucible and the ceramic and metal particles inside to 700°C at a heating rate of 20°C / min and keep warm for 10 minutes. Then, slowly press the molten aluminum alloy into the interconnected pores of the porous ceramic matrix under loading force, and then slowly cool to room temperature. Step 5: Post-treatment: Use solid solution and aging treatment to eliminate the internal stress of the ceramic / metal composite component and stabilize the microstructure.

[0009] Furthermore, the solution treatment process in step five is to keep the temperature at 470° C. for 10 hours, and the subsequent aging treatment process is to keep the temperature at 140° C. for 24 hours.

[0010] Furthermore, the network ceramic / metal composite component manufacturing process based on the high temperature impregnation process can design the porosity of the porous ceramic matrix in the network ceramic / metal composite protection unit according to the working environment and adjust the ceramic / metal ratio.

[0011] Compared with the prior art, the present invention has the following beneficial effects: The present invention can control porous structures of different pore sizes through 3D modeling software design, including lattice structure, TPMS structure, and Voronoi structure. It is an excellent structure with high impact resistance, high energy absorption and light weight; among them, the TPMS structure has a higher elastic modulus, which can reduce the deformation of the ceramic structure during the load-bearing process, and the Voronoi structure has a higher compressive strength.

[0012] The blank forming process adopted in the present invention is photo-curing forming technology, which can support the forming of complex structures and ensure the uniformity of the material in the blank. The subsequent heat treatment process ensures that the final sample has lower internal stress. It has been applied in nuclear protection devices, communications and other fields.

[0013] The high-temperature impregnation process adopted in the present invention can ensure that the molten metal aluminum is evenly distributed in the pores of the porous ceramic matrix, and the added copper oxide additive can form a CuAlO2 second phase during the high-temperature impregnation process, which serves as a transition phase at the ceramic-metal interface, runs through the two materials, strengthens the interface bonding strength, and realizes a three-dimensional continuous ceramic / metal composite structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a process flow chart of the preparation of the network ceramic / metal composite component of the present invention;

[0015] Figure 2 This is a sample diagram of a network ceramic / metal composite component of the present invention;

[0016] Figure 3 This is a microscopic morphology of the porous ceramic matrix before and after the powder copper oxide modification of the present invention;

[0017] Figure 4 It is a diagram showing the dynamics simulation results of different porous matrix structures of the network ceramic / metal composite structure of the present invention;

[0018] Figure 5 It is a lead bullet impact clamping method and a test result diagram of the network ceramic / metal composite component of the present invention;

[0019] Figure 6 This is a unitized application research diagram of the network ceramic / metal composite component of the present invention. DETAILED DESCRIPTION

[0020] In order to clearly understand the above-mentioned objects, features and advantages of the present invention, the scheme of the present invention is further described below.

[0021] like Figure 1 As shown, the invention discloses a network ceramic / metal composite component manufacturing process based on a high temperature impregnation process, wherein the preparation method comprises the following steps:

[0022] Step 1: Use 3D modeling software to build a ceramic skeleton model. The size of a single cell structure of porous ceramics is 4 mm, and the overall size is 36 mm × 42 mm × 20 mm, and then export it as an STL file; special structures with different pore sizes include lattice structure, TPMS structure, and Voronoi structure.

[0023] Step 2: Add CuO and NaOH to deionized water in a mass ratio of 1:1.3. After cooling, add copper sulfate to the solution in a CuO:Al2(SO4)3 mass ratio of 1:2.2. After magnetic stirring, filter to obtain Al(OH)3-coated CuO. Finally, calcine the filtrate at 300°C for 2h, at which time Al(OH)3 decomposes into Al2O3 to obtain Al2O3-coated copper oxide. Mix alumina, coated copper oxide powder, photosensitive resin, and dispersant in a planetary ball mill at a ratio of 96:4:40:2 at a speed of 600rpm for 60min to obtain a uniform slurry. Step 3, placing the slurry prepared in the above step 2 into a photocuring printer, and importing the STL file obtained in step 1, the printing light intensity is 2.44mJ / cm2, the exposure time is 15s, the printing layer thickness is 0.05mm, and the ceramic body is printed. The ceramic body is immersed in alcohol for ultrasonic cleaning for 5min, and placed in a UV air dryer for secondary curing for 10min. The body is placed in a degreasing furnace, and the temperature is set as follows: 0-600℃ in the degreasing stage, and kept at 90℃, 120℃, 160℃, 240℃, 340℃, 410℃, 500℃, and 600℃ for two hours respectively, and the heating rate is set to 0.5℃ / min. After cooling, the body is taken out and placed in a sintering furnace. The heating rate in the sintering stage is selected to be 3℃ / min, and it is kept at 1600℃ for two hours. After cooling with the furnace, it is taken out to obtain a ceramic bracket; Step 4: Take out the aluminum alloy particles, grind them with silicon carbide powder, and immerse them in alcohol ultrasonic cleaning for 10 minutes. Put the ceramic bracket in step 3 together with the aluminum alloy particles and the loading block into the graphite crucible, close the furnace air inlet, turn on the vacuum pump to exhaust air from the exhaust port until the air pressure is close to vacuum, turn off the vacuum pump and flush argon from the air inlet to reach 0.1MPa, cycle the above operations twice, raise the temperature to 700℃ at a heating rate of 20℃ / min and keep it warm for 10 minutes, then slowly cool to room temperature. Step 5: Treat the components after high-temperature impregnation by solution treatment, raise the temperature to 470°C and keep it for 10 hours; then keep it at 140°C for 24 hours for aging treatment, and take it out after cooling to obtain a network ceramic / metal composite component.

[0024] The porous ceramic substrate after sintering in this embodiment was subjected to SEM detection. Compared with the alumina sintering without copper oxide modification, the density of the modified microstructure was obviously increased.

[0025] For three different ceramic / metal composite components, lattice structure, TPMS structure, and Voronoi structure, simulation analysis is performed to evaluate their impact resistance. A high-speed incident object with an initial velocity of 400m / s is set on the surface of the composite structure. The stress distribution of different structures at different time nodes is shown in the following figure. Figure 4 As shown, the Voronoi structure produces cracks inside the ceramic structure under stress, and the metal material produces compression deformation. Under the combined action of the two, the structure forms a metal-wrapped ceramic fragment shape, ensuring its ability to resist impact loads. The TPMS structure has better elasticity than the Voronoi structure, while the lattice structure ceramic skeleton has poor mechanical properties, so its impact resistance is relatively poor.

[0026] For the network ceramic / metal composite component prepared by the high temperature impregnation process in the example of the present invention, a TPMS structure with a better simulation structure was selected, and a light fire test was designed. The component was embedded in the substrate and a live ammunition test was carried out using lead bullets. The bullet speed was 400m / s and the shooting distance was 10m. The lead bullet test results are as follows: Figure 5 As shown, the impact point is located at the edge of the composite component. The instantaneous impact force and high temperature brought by the high-speed bullet compress the aluminum alloy area of ​​the composite component, and the material migrates to the surrounding areas. At the same time, due to the lower hardness of the lead bullet, the lead bullet causes less damage to the ceramic.

[0027] Figure 6 This is a preliminary study on the application of unitization of network ceramic / metal composite components formed by the high temperature infusion process of the present invention.

[0028] The above are only preferred embodiments of the present invention, but the technical features of the present invention are not limited thereto. It should be pointed out that any simple changes, equivalent replacements, etc. made based on the present invention to achieve basically the same technical effects are all within the protection scope of the present invention.

Claims

1. A method for preparing a porous ceramic substrate, characterized in that: The steps of the method are as follows Step 1: Modeling: Design porous models with different pore sizes and structures to model the ceramic porous matrix; Step 2, slurry preparation: mixing ceramic powder with additives to obtain mixed ceramic powder, adding the mixed ceramic powder and alumina powder to photosensitive resin and dispersant, stirring and mixing to obtain a uniform slurry; Step 3: green body forming: import the model established in step 1 into the light-curing 3D printer, place the slurry obtained in step 2 into the printer, obtain a ceramic green body by light-curing forming, place the obtained green body in alcohol for ultrasonic cleaning for 5 minutes to remove the uncured slurry on the surface, and then place it in a UV air dryer for curing and air drying for 10 minutes to reduce the internal stress of the green body; Step 4: Degreasing and sintering: Degreasing and sintering the ceramic body obtained in step 3, and taking it out after cooling in the furnace to obtain a porous ceramic matrix.

2. A manufacturing process for a network ceramic / metal composite component formed by a high temperature impregnation process, characterized in that: The steps of the method are as follows Step 1: Pretreatment: Weigh a certain mass of aluminum alloy particles, grind them with silicon carbide powder, immerse them in alcohol and use ultrasonic cleaning to remove the oxide layer on the surface; Step 2, loading: placing the aluminum alloy particles obtained in step 1 on top of the porous ceramic substrate obtained in claim 1 and placing them together in a graphite crucible, loading them into a furnace and placing a zirconium oxide loading block; Step 3: Gas washing: Close the furnace air inlet, turn on the vacuum pump to extract air from the exhaust port until the air pressure is close to vacuum, turn off the vacuum pump and flush argon gas from the air inlet to reach a standard atmospheric pressure, and repeat the above operation twice; Step 4: High-temperature immersion: Heat the crucible and the ceramic and metal particles inside to 700°C at a heating rate of 20°C / min and keep warm for 10 minutes. Then, slowly press the molten aluminum alloy into the interconnected pores of the porous ceramic matrix under loading force, and then slowly cool to room temperature. Step 5: Post-treatment: using solid solution and aging treatment to eliminate the internal stress of the ceramic / metal composite component, stabilize the microstructure, and obtain a network ceramic / metal composite component.

3. Furthermore, according to the method for preparing a porous ceramic substrate according to claim 1, it is characterized in that: The porous structures with different pore sizes in step 1 include lattice structures, TPMS structures, and Voronoi structures.

4. Furthermore, according to the method for preparing a porous ceramic substrate according to claim 1, it is characterized in that: In the step 2, the ceramic powder can be alumina, and the additive is copper oxide. When the alumina is sintered, a liquid phase is generated to promote material transfer and compact the internal structure of the matrix.

5. Furthermore, according to the method for preparing a porous ceramic substrate according to claim 1, it is characterized in that: The powder mixing method in step 2 is a chemical coprecipitation method, which can coat aluminum oxide on the surface of copper oxide compared to the ball milling mixing method, thereby reducing the light absorption of copper oxide during the photocuring process.

6. Further, according to the manufacturing process of a network ceramic / metal composite component formed by a high temperature impregnation process as described in claim 2, it is characterized in that: In the step three, in order to prevent the metal with a lower melting point than the ceramic bracket from reacting with oxygen for oxidation under high temperature conditions, a 0.1MPa argon atmosphere is adopted to complete the process described in this step. In order to avoid bubbles and defects inside the metal, a zirconium oxide loading block is placed above the ceramic bracket and the metal ingot and placed in the mold together.

7. Further, according to the manufacturing process of a network ceramic / metal composite component formed by a high temperature impregnation process as described in claim 2, it is characterized in that: The insulation temperature in the step 4 is 700° C. according to differential scanning calorimetry (DSC) analysis, and the loading force is 3 MPa and 1 mm / min, ensuring that the molten aluminum alloy evenly immerses the porous ceramic body.

8. Further, according to the manufacturing process of a network ceramic / metal composite component formed by a high temperature impregnation process as described in claim 2, it is characterized in that: The solution treatment process in step six is ​​to keep the temperature at 470° C. for 10 hours, and the subsequent aging treatment process is to keep the temperature at 140° C. for 24 hours.

9. Furthermore, according to the method for preparing a network ceramic / metal composite component formed by a high temperature impregnation process as claimed in claim 2, it is characterized in that: The copper oxide added to the network ceramic / metal composite component forms a second phase penetrating both the ceramic and metal materials during the high-temperature impregnation process, thereby improving the ceramic-metal interface bonding strength.